(3TQM bUjOI HGfJ SYGOs - (3dYHO Gddg Hf SdGeI GdCOcGhi GTGaYis; (3cYH Hf RgjQ , CHh GdeZQH,J (B26 (3g` s ((3UGdM Hf Ydi GdbdYi Gdeci s)
(3ChdgG (B:s
(3hHYO abO CeQfi ef WGYJg Ydi hGLHg MVQI CejQ GddhGA GdTQja GdSdWGfi , CejQ GdMGL GdTQja YKeGf Hjc hHCf CdNU ef TQM bUjOI cYH s
(3BNQgG (B:s
(3hgPG BNQ GdbUjOg GdeHGQcg bO GfJgi eG CNJQJg ef eMGSf gPG GdJdNjU gPG hEf de jcf di ajeG JQGA ef GdePjO EdG VHW CdaGXg GddZhjg hgfG La Qjb GdjQGY s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3dNU ajg TQM LdGd GdOjf GdSjhWi ddbUjOg GdeSei (B" (3cfg GdeQGO ai HjGf HGfJ SYGO (B" (3hSeGg eGdGHO efg ef eQGO Gdcfg hHChdgG Jedc HJGQjN (B1161 (3h (B1238 (3h (B1243(3g`s
(3fSNI KGfjgs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs